(untitled) (Praxis Educativa, 2012)
This paper explores how teachers’ representations mediate their interpretation of the prescribed curriculum and their creation of syllabi in the EFL Teacher Education Program in the School of Humanities, Mar del Plata State University, Argentina. Bourdieu’s analytic notion of habitus is employed to interpret these views, derived from actors’ narratives. Data were gathered during semi flexible interviews administered to a selection of four professors. Results suggest that instructors pedagogically translate the prescribed curriculum. Bourdieu’s categories indicate how each professor’s curriculum stems from an objectively obtained lector or auctor habitus. In the pedagogic translation carried out there emerges the domesticated curriculum—or the exercise of symbolic violence. Finally, although this research has a limited number of subjects and is interpretive in character, teachers’ representations nevertheless surface as curricular content. Regarding future applications, theorizing on these problematics would allow for their treatment in peer communities aimed at achieving harmonically diverse curricula